(untitled) (Jurnal Kemanusiaan, 2017)
The study includes three government agencies, namely the Royal Malaysian Police (RMP), the National Registration Department (NRD) and the Public Works Department (PWD) in Malaysia. Studies on these three government agencies covered the services provided by these agencies, the function of these agencies, as well as the effectiveness and efficiency their officers. A total of 270 respondents from the three government agencies, namely the Royal Malaysian Police (RMP), the National Registration Department (NRD) and the Public Works Department (PWD) in Malaysia have been selected to answer the questionnaire in this study. The results of this study demonstrate the job effectiveness and workerâ€™s effectiveness have a positive relationship with service innovation. Meanwhile, labour productivity showed a significant partial correlation with service innovation. Therefore, efforts to promote service innovations should be continued by the Government of Malaysia in agencies so that employee work quality can be further improved. Kajian ini merangkumi tiga agensi kerajaan iaitu Polis DiRaja Malaysia (PDRM), Jabatan Pendaftaran Negara (JPN) dan Jabatan Kerja Raya (JKR) di Malaysia. Kajian ke atas tiga buah agensi kerajaan ini adalah merangkumi perkhidmatan yang diberikan oleh agensi-agensi tersebut, fungsi agensi-agensi tersebut, serta keberkesanan dan kecekapan pengawai yang bertugas di agensi-agensi tersebut. Seramai 270 responden dari tiga buah agensi kerajaan iaitu Polis DiRaja Malaysia (PDRM), Jabatan Pendaftaran Negara (JPN) dan Jabatan Kerja Raya (JKR) di Malaysia telah dipilih untuk menjawab soal selidik dalam kajian ini. Hasil kajian ini menunjukkan keberkesanan kerja dan keberkesanan kerja seseorang pekerja mempunyai hubungan positif dengan pembaharuan dalam bidang kerja. Manakala, produktiviti kerja menunjukkan hubungan separa signifikan dengan pembaharuan dalam bidang kerja. Oleh itu, usaha untuk memperkenalkan lagi pembaharuan dalam bidang kerja harus diteruskan oleh Kerajaan Malaysia di agensi-agensi kerajaan supaya kualiti kerja cemerlang seseorang pekerja boleh dipertingkatkan lagi. Â